Korhogo motorcycle taxi contractors facing taxes (International Journal of Scientific Research and Management (IJSRM), 2022)
The objective of this text is to analyze the power relations between the tax administration and the entrepreneurs of Taxis- motos in the context of the collection of taxes relating to public transport activities in Korhogo . The qualitative approach was favored in the production and analysis of data. The results were produced from interviews carried out with motorcycle taxi entrepreneurs, city hall officials and tax officials. The interviews were transcribed and edited manually. We have proceeded to the analysis of the discourses, strategies and logics which constitute the register of action of each stakeholder at work in the governance of motorcycle taxis. Born in a context of strong mobility constraints, in the first hours of the socio-political crisis of 2002, Korhogo’s motorcycle taxis gradually established themselves as key players in the city’s urban landscape. The strong commitment of young urban and rural people to this activity, due to the generalized situation of unemployment, gave it a boost and prompted “the new self-proclaimed authorities” of the city to take it over to organize it. Thus, for more than a decade, Korhogo’s motorcycle taxis have evolved in a climate of near-freedom. After the reunification of the country, the State adopted an action matrix favoring the employment of ex-combatants and young people at risk. It extends this register of favors enjoyed by motorcycle taxi entrepreneurs through tolerance vis-à-vis tax obligations. Recently, his desire to apply the tax provisions relating to the transport sector has met with opposition from taxi-motorcycle entrepreneurs who refuse to leave their enclave of freedom established by the war. In this situation, they mobilize resources to stay in their lawless zone.